The effect of supply chain linkage on micro and small enterprises’ performance - Ya’kob, Siti Aisyah; Wan Jusoh, Wan Jamaliah (Universiti Malaysia Sarawak, 2016)
The practice of linking the enterprises with their channel members through supply chain activities is meant to achieve better performance and to create a win-win situation for both sides. A study on supply chain linkages is necessary in order to observe the effect of the linkages on firms’ performance. Therefore, this study is conducted to examine the factors of supply chain linkages that affect the business performance among micro and small enterprises. Three factors were proposed, which are information sharing, development programme and outsourcing. A total of 214 sets of questionnaires was completed by owners and firm’s personnel from 13 industrial sectors. The findings from this study revealed that information sharing and development programme have a significant and positive relationship with firms’ performance. Even though outsourcing shows a positive relationship with firms’ performance, but the elationship was not statistically significant. The results provide a better understanding of information sharing, development programme and outsourcing from micro and small enterprise perspective in Sarawak.